An effective acid combination for enhanced properties and corrosion control of acidizing sandstone formation - Shafiq, Mian Umer; Ben Mahmud, Hisham (IOP Publishing in Bristol, UK, 2016)
To fulfill the demand of the world energy, more technologies to enhance the recovery of oil production are being developed. Sandstone acidizing has been introduced and it acts as one of the important means to increase oil and gas production. Sandstone acidizing operation generally uses acids, which create or enlarge the flow channels of formation around the wellbore. In sandstone matrix acidizing, acids are injected into the formation at a pressure below the formation fracturing pressure, in which the injected acids react with mineral particles that may restrict the flow of hydrocarbons. Most common combination is Hydrofluoric Acid - Hydrochloric with concentration (3% HF - 12% HCl) known as mud acid. But there are some problems associated with the use of mud acid i.e., corrosion, precipitation. In this paper several new combinations of acids were experimentally screened to identify the most effective combination. The combinations used consist of fluoboric, phosphoric, formic and hydrofluoric acids. Cores were allowed to react with these combinations and results are compared with the mud acid. The parameters, which are analyzed, are Improved Permeability Ratio, strength and mineralogy. The analysis showed that the new acid combination has the potential to be used in sandstone acidizing.